2019
DOI: 10.1038/s41598-019-50958-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-like cryotherapy improves footprint patterns and reduces synovial inflammation in a rat model of post-traumatic knee osteoarthritis

Abstract: Cryotherapy is a non-pharmacological treatment commonly used to control inflammation and improve function after acute traumas. However, there are no definitive findings about its effects on chronic joint diseases such as knee osteoarthritis (KOA). The aim of this study was to investigate the effects of clinical-like cryotherapy on functional impairment and synovial inflammation in a rat model of KOA generated by anterior cruciate ligament transection (ACLT). Thirty-two male Wistar rats were randomly divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
(63 reference statements)
1
16
0
Order By: Relevance
“…Using p16-3MR transgenic mice, Jeon et al [41] demonstrated that selective removal of senescent cells retards OA progression, reduces pain, and creates a pro-regenerative environment. Nonpharmacological treatments such as cryotherapy improve footprint patterns and reduce synovial inflammation [42]. Weight loss is often recommended in treatment programs, as it decreases joint loading and IL-7 levels through biomechanical and inflammatory pathways [11].…”
Section: Treatment Of Ptoamentioning
confidence: 99%
“…Using p16-3MR transgenic mice, Jeon et al [41] demonstrated that selective removal of senescent cells retards OA progression, reduces pain, and creates a pro-regenerative environment. Nonpharmacological treatments such as cryotherapy improve footprint patterns and reduce synovial inflammation [42]. Weight loss is often recommended in treatment programs, as it decreases joint loading and IL-7 levels through biomechanical and inflammatory pathways [11].…”
Section: Treatment Of Ptoamentioning
confidence: 99%
“…Clinical-like cryotherapy reduced signs of joint inflammation in a mouse model of KOA, decreasing the number of leukocytes and levels of cytokines in the synovial fluid [ 14 ]. In a previous study by Castro et al [ 16 ], clinical-like cryotherapy in a mouse model of acute knee arthritis also showed decreased inflammatory signs of joint swelling, neutrophil migration, and levels of cytokines IL-6, IL-1 β , and TNF- α in the synovial fluid [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tibiofemoral joint thickness (in mm) was measured two hours after the second clinical-like cryotherapy session and under anesthesia (O 2 2 L/m, 2% isoflurane) using an electronic digital caliper (Digimatic ABSOLUTE 150 mm, Mitutoyo, Japan). The mean of three measures was included in the data analysis [ 14 , 15 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studying the possible effects of cryotherapy in an arthritis model may be useful for clinical practice. The ice pack was considered a welltolerated modality of therapy (7), and it was effective to ameliorate joint and muscle damage in chronic models of transection of the anterior cruciate ligament (8).…”
Section: Introductionmentioning
confidence: 99%